2023
DOI: 10.1371/journal.pone.0286373
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 spike protein diversity at an intra-host level, among SARS-CoV-2 infected individuals in South Africa, 2020 to 2022

Abstract: Intra-host diversity studies are used to characterise the mutational heterogeneity of SARS-CoV-2 infections in order to understand the impact of virus-host adaptations. This study investigated the frequency and diversity of the spike (S) protein mutations within SARS-CoV-2 infected South African individuals. The study included SARS-CoV-2 respiratory samples, from individuals of all ages, received at the National Health Laboratory Service at Charlotte Maxeke Johannesburg Academic hospital, Gauteng, South Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…A novel SARS-CoV-2 variant B.1.1.529 was identified in Southern Africa and flagged as containing a potentially concerning number of spike mutations on 23rd November 2021 following sequence identification in Botswana (3 genomes), and Hong Kong ex S. Africa (1 genome, partial) 20 . South African public health recorded an extremely large and rapid increase in SARS-CoV-2 cases and test positivity in Gauteng Province for the week of 14–20 November 2021 21 with this rapidly attributed to Omicron by South Africa Centre for Epidemic Response and Innovation 22 , 23 . It was designated by WHO and named Omicron VOC on 26th November 2021.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel SARS-CoV-2 variant B.1.1.529 was identified in Southern Africa and flagged as containing a potentially concerning number of spike mutations on 23rd November 2021 following sequence identification in Botswana (3 genomes), and Hong Kong ex S. Africa (1 genome, partial) 20 . South African public health recorded an extremely large and rapid increase in SARS-CoV-2 cases and test positivity in Gauteng Province for the week of 14–20 November 2021 21 with this rapidly attributed to Omicron by South Africa Centre for Epidemic Response and Innovation 22 , 23 . It was designated by WHO and named Omicron VOC on 26th November 2021.…”
Section: Resultsmentioning
confidence: 99%
“…A novel SARS-CoV-2 variant B.1.1.529 was identified in Southern Africa and flagged as containing a potentially concerning number of spike mutations on 23rd November 2021 following sequence identification in Botswana (3 genomes), and Hong Kong ex S. Africa (1 genome, partial) 20 . South African public health recorded an extremely large and rapid increase in SARS-CoV-2 cases and test positivity in Gauteng Province for the week of 14-20 November 2021 21 with this rapidly attributed to Omicron by South Africa Centre for Epidemic Response and Innovation 22,23 www.nature.com/scientificreports/ coverage 24 and early laboratory studies indicated significant reduction in neutralising ability of vaccine and prior-infection induced antibodies [25][26][27] . This reinfection and incomplete vaccine protection risk has been borne out in populations of higher vaccination coverage following Omicron introduction in the U.K. with the variant rapidly becoming dominant against a background of high Delta caseload.…”
Section: Detection Of Omicron Variant and Subvariantsmentioning
confidence: 99%